The establishment of banking supervision in Italy: an assessment (1926–1936) - Molteni, M; Pellegrino, D (Routledge, 2022)
This paper describes the establishment of banking supervision in Italy and its operation between 1926 and 1936, using a narrative approach based on previously classified documents from the Bank of Italy’s Historical Archives. This case is particularly interesting from the international perspective, Italy having been the first European country to assign substantial supervision to its central bank, a few years before the 1929 crisis. Notwithstanding insufficient regulation and a light touch concerning the four major mixed banks, we document considerable enforcement of the law, which went beyond the initial provisions, thanks to the rather proactive supervisory approach adopted by the Bank of Italy.